Echocardiographic Findings and Their Impact on Outcomes of Critically Ill Patients with AIDS in the Era of HAART - Abubakr A. Bajwa; James D. Cury; Lisa Jones; Adil Shujaat; Faisal Usman (Pulmonary Medicine)
Objective. To describe the echocardiographic findings in critically ill patients with AIDS and their impact on clinical outcome. Design. A retrospective chart review of consecutive AIDS patients over 18 years of age, who had a trans-thoracic echocardiogram performed during the course of intensive care unit stay over the course of 2 years at a tertiary care hospital. Main outcome measures. The prevalence of echocardiogram abnormalities in this population and its impact on ICU mortality, ICU length of stay, hospital mortality, hospital length of stay and 60 day survival. Results. Among 107 patients who met the inclusion criteria, an admission echocardiogram was performed in 62 (58%). The prevalence of cardiac abnormalities was 60%. The most common admission diagnosis was respiratory failure 𝑛=27 (43%). The most common finding on echocardiogram was left ventricular (LV) dysfunction 𝑛=31 (50%) followed by pulmonary hypertension 𝑛=25 (40%). None of these findings had a significant impact on clinical outcomes. There was trend toward reduced 60 day survival among patients with depressed LV function. Conclusions. Although echocardiogram abnormalities were prevalent among this population none of these findings had a significant impact on ICU mortality or hospital mortality and ICU length of stay or hospital length of stay.